What the Pandemic Means: Perspectives from the Trinity Long Room Hub Covid-19 Blog Collection - Erickson, Jacob; Lyons, Donna; Grile, Courtney Helen; Devitt, Ann; Slote, Samuel; Patten, Eve; Payne, Elspeth; Ahmed, Sahar; Hendley Rooney, Daryl; Leeson, Lorraine (Trinity Long Room Hub Arts and Humanities Research Institute, 2021)
In the spring of 2020, when the pandemic hit our shores, we were told to stay home. We listened to public health advice and to experts debating the measures required to protect us. Scientific terminology crept into our daily conversations. But in addition to the ongoing uncertainty about the long-term impacts of the virus on our health, many of us were struggling with the uncertainty that now emerged in our everyday lives. What did the pandemic mean to us, beyond its medical impact, in a cultural and social sense? To consider this question, the Trinity Long Room Hub launched a Covid-19 blog series, in which contributors reflected on how we might cope with the loss of physical contact and human connection (Courtney Helen Grile, p.16) and how we could feel both ‘urgency and fatigue’ (Jacob Erikson, p.8). We heard from author Caitríona Lally on how our understanding of ‘essential work’ changes at a time like this (p.5), and Sam Slote talked us through Ulysses as a guide for navigating the pandemic as we celebrated ‘Zoomsday’ (p.23). Lorraine Leeson highlighted what it means to be deaf during a global health crisis, (p.45) and Eve Patten drew on post-war literature to reflect on what might come next: ‘A Tale of ‘Afterwards’’ ( p.53). In these and other blogs from the series, we looked to language and literature, to art and creative practice, and to many other humanities disciplines in search of precedent and perspective on what the pandemic means for us as humans. We are pleased to be able to share these blogs with you in this shortened collection.
PUBLISHED
Artwork: Rita Duffy
Trinity Long Room Hub, Trinity College Dublin
Keywords: education; Literature; Joyce; First World War; Culture; Covid-19; pandemic; humanities; social change; social justice; human rights; religion; history of medicine; deaf; inclusion; democracy; art; creative arts practice; European Union politics; Connection; understanding; identity; Dorothy Stopford Price; languages; ecology; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Identities in Transformation; Inclusive Society; International Development; International Integration; Making Ireland; Manuscript, Book and Print Cultures; 20th Century literature; 20th century Irish history; ART; ART COLLECTION; ARTS/HUMANITIES/CULTURAL ACTIVITIES; Access for the Deaf Community; CONNECTIONS; COVID 19; COVID 19 Pandemic; COVID-19; Civil/Human Rights; Computers & Education; Creative arts practice; DEAF; DEMOCRACY; Deaf Community and Culture; Deaf Education; Deaf Studies; Deaf interpreters; Deaf interpreters (DI); Deaf women; Democracy, elections, political parties, representation; Disconnection; EUROPEAN UNION; Education in ireland; Emotional Understanding; European Convention on Human Rights; European Identity; European Union Politics; First World War literature and propaganda; Governance, Human Rights, European Union Law; Higher Education Policy; History of Ireland; History of Medicine; History of women; Human Rights; Human Rights Law; Humanities; IDENTITY; Identity politics and social change; Inter-Arts--Interdisciplinary Art Forms; Interdisciplinary research; Irish cultural identity; Irish health system; Italian Literature; James Joyce; Language and Identity; Law and Social Change; Law and religion; Literature; Literature and History; Medical Humanities; Modern Irish and British Literature, esp. James Joyce.; On line information services, Democracy, Business; Pandemic; Political change, identity and the urban sphere; Religion; Religion and Culture; Religion in pluralist democracies; Religion in the Public Sphere; Religious culture & national identity; SELF AND IDENTITY; SOCIETY AND LITERATURE; Social Change; Transdiciplinary